2013
DOI: 10.1037/a0032200
|View full text |Cite|
|
Sign up to set email alerts
|

Mindfulness-based stress reduction and physiological activity during acute stress: A randomized controlled trial.

Abstract: MBSR may help reducing blood pressure levels and blood pressure reactivity to stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
114
4
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(129 citation statements)
references
References 17 publications
(23 reference statements)
2
114
4
4
Order By: Relevance
“…Whereas previous research shows that 8 weeks (but not 3 sessions) of mindfulness training reduces biological stress reactivity Nyklíček et al, 2013), we now show that an intermediate dose -two weeks of daily mindfulness training plus a booster session -is effective for reducing biological reactivity.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Whereas previous research shows that 8 weeks (but not 3 sessions) of mindfulness training reduces biological stress reactivity Nyklíček et al, 2013), we now show that an intermediate dose -two weeks of daily mindfulness training plus a booster session -is effective for reducing biological reactivity.…”
Section: Discussioncontrasting
confidence: 93%
“…For example, eight-week mindfulness interventions have been shown to reduce physiological and subjective reactivity to acute stress challenge tasks (Britton et al, 2012;Hoge et al, 2013;Nyklíček et al, 2013). Still, little is known about the active mechanisms of mindfulness interventions that drive these stress reduction effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulating attention towards distressing cognitions and emotions is a coping strategy taught to distressed individuals in current therapeutic paradigms such as Mindfulness-Based Stress Reduction (Nyklíček et al, 2013) and acceptance and commitment therapy (Hayes et al, 2006). However, there is little psychophysiological evidence for the effectiveness of attention regulation in modulating the stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Recent theoretical and empirical developments suggest that perfectionism and perseverative cognitions can be reduced by cognitive-behavioral therapy and mindfulness meditation (Delgado et al, 2010;Masuda and Tully, 2012;Nyklíček et al, 2013). A recent randomized controlled-trial adopting both approaches to treat maladaptive perfectionists revealed significant reductions in anxiety sensitivity and negative automatic thoughts (Radhu et al, 2012a;Guglietti et al, 2013).…”
Section: Introductionmentioning
confidence: 99%